Menu of services : technical assistance provided by UNODC (UNODC ViennaAT, 2007)
Describes the legal, analytical and technical capabilities the office can offer and the tools it has available to achieve the overall objectives set out in its strategy for 2008-2011.
Keywords: DRUGS OF ABUSE